Suggestions for authors of medical articles - Péricles Maranhão-Filho (Arquivos de Neuro-Psiquiatria)
ABSTRACT This manuscript is directed to those interested in writing medical articles. The author advises the use of certain conventions giving specific suggestions in homogenize the language of manuscripts whose purpose is their publication in specialized journals.